2016
DOI: 10.1155/2016/4680543
|View full text |Cite
|
Sign up to set email alerts
|

The Palliative Management of Refractory Cirrhotic Ascites Using the PleurX©Catheter

Abstract: Background. Treatment options are limited for patients with refractory cirrhotic ascites (RCA). As such, we assessed the safety and effectiveness of the PleurX catheter for RCA. Methods. A retrospective analysis was performed on all patients with RCA who have undergone insertion of the PleurX catheter between 2007 and 2014 at our clinic. Results. Thirty-three patients with RCA were included in the study; 4 patients were lost to follow-up. All patients were still symptomatic despite bimonthly large volume parac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(76 citation statements)
references
References 28 publications
3
72
1
Order By: Relevance
“…In one study with the highest prevalence of positive ascitic cultures (42%, n = 14), further clarification sought from Reinglas et al confirmed that, in addition to sampling ascitic fluid in symptomatic patients, samples were also taken routinely throughout. It was unclear if these were taken from the PIPC or the abdomen.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In one study with the highest prevalence of positive ascitic cultures (42%, n = 14), further clarification sought from Reinglas et al confirmed that, in addition to sampling ascitic fluid in symptomatic patients, samples were also taken routinely throughout. It was unclear if these were taken from the PIPC or the abdomen.…”
Section: Resultsmentioning
confidence: 98%
“…Rates of BP varied from 0% to 42% across individual studies with an overall combined rate of 17% (29/166). Excluding the 11 patients in Reinglas et al with catheter related organisms, the overall rate of BP was 12.7% (21 patients). If the Reinglas study was excluded as an outlier, the overall rate of BP across the remaining 15 studies was 11% (15/133).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ascites management comprises a stepwise approach of (i) salt restriction, (ii) diuretic therapy, (iii) large volume paracentesis with albumin substitution, (iv) transjugular intrahepatic portosystemic shunt (TIPS) and ultimately, (v) liver transplantation . Efficacy and safety of novel therapeutic approaches, such as low‐flow pump systems to remove ascites from the peritoneal cavity into the bladder or the insertion of tunnelled catheters, remain to be established . According to treatment response, ascites is grouped into uncomplicated/manageable or refractory ascites.…”
Section: Introductionmentioning
confidence: 99%